2013
DOI: 10.1128/aem.03253-12
|View full text |Cite
|
Sign up to set email alerts
|

Single Amino Acid Substitutions in HXT2.4 from Scheffersomyces stipitis Lead to Improved Cellobiose Fermentation by Engineered Saccharomyces cerevisiae

Abstract: f Saccharomyces cerevisiae cannot utilize cellobiose, but this yeast can be engineered to ferment cellobiose by introducing both cellodextrin transporter (cdt-1) and intracellular ␤-glucosidase (gh1-1) genes from Neurospora crassa. Here, we report that an engineered S. cerevisiae strain expressing the putative hexose transporter gene HXT2.4 from Scheffersomyces stipitis and gh1-1 can also ferment cellobiose. This result suggests that HXT2.4p may function as a cellobiose transporter when HXT2.4 is overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…These results demonstrated that mutations at specific residues (e.g., Phe 40 in C. intermedia GXS1) can have a significant impact on the carbohydrate selectivity of these MFS transporters. The fact that single amino acid substitutions can have such a significant impact on transport phenotype (38)(39)(40) indicates how simple homology based searches can be ineffective at identifying efficient xylose transporters (35,36). However, evidence of natural xylose exclusivity is seen in the Escherichia coli xylE transporter that has recently been crystallized (41).…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…These results demonstrated that mutations at specific residues (e.g., Phe 40 in C. intermedia GXS1) can have a significant impact on the carbohydrate selectivity of these MFS transporters. The fact that single amino acid substitutions can have such a significant impact on transport phenotype (38)(39)(40) indicates how simple homology based searches can be ineffective at identifying efficient xylose transporters (35,36). However, evidence of natural xylose exclusivity is seen in the Escherichia coli xylE transporter that has recently been crystallized (41).…”
mentioning
confidence: 80%
“…As an alternative to bioprospecting, we have previously reported that xylose affinity and exponential growth rates on xylose can be improved via directed evolution of Candida intermedia glucose-xylose symporter 1 (GXS1) and Scheffersomyces stipitis xylose uptake 3 (XUT3) (38). These results demonstrated that mutations at specific residues (e.g., Phe 40 in C. intermedia GXS1) can have a significant impact on the carbohydrate selectivity of these MFS transporters. The fact that single amino acid substitutions can have such a significant impact on transport phenotype (38)(39)(40) indicates how simple homology based searches can be ineffective at identifying efficient xylose transporters (35,36).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…By contrast, cellobiose is an unusual substrate for S. cerevisiae, and is therefore not recognized as a readily fermentable sugar like glucose. Efforts to optimize cellobiose fermentation in engineered S. cerevisiae through combinatorial transcriptional engineering [11], experimental evolution [29], or by exploring and evolving new cellodextrin transporters [12,14,30,31] or an alternative cellobiose phosphorylase Figure 1 Suboptimal cellobiose metabolism in engineered Saccharomyces cerevisiae. (A) Fermentation profiles of recombinant cellobiose-utilizing S. cerevisiae with plasmid pRS426-BT on cellobiose or glucose in anaerobic conditions with an initial OD 600 of 1.…”
Section: Introductionmentioning
confidence: 99%